Guided Inquiry Learning Model Using Scientific Argumentation Activities to Improve Concept Understanding on Optical and Light (Jurnal Pendidikan Fisika Indonesia, 2023)
Problem-solving ability, as one of the most important skills in the 21st century, must be improved to face the various challenges that exist. This is because solving problems requires mastery of the concepts underlying them. One learning model that can improve conceptual understanding is guided inquiry using scientific argumentation activities. This study aims to analyze the effectiveness of the guided inquiry learning model using scientific argumentation activities to improve junior high school students' conceptual understanding. This quasi-experimental study used a non-equivalent control group design. The results of data analysis using the Wilcoxon test showed that there were significant differences in the pretest and posttest of each class before and after treatment. The results of the Mann-Whitney test at the pretest showed that there was no significant difference, while the posttest showed that there were significant differences between the control class and the experimental class. The results of the N-Gain test in the experimental class in the high category indicate that the use of guided inquiry with scientific argumentation activities could increase students' conceptual understanding more than in the control class in the medium category. The result of the effect size test showed that the use of guided inquiry with scientific argumentation activities has a moderate effect on students' understanding of concepts.